TGF-β mRNA levels in circulating extracellular vesicles are associated with response to anti-PD1 treatment in metastatic melanoma - Crucitta, Stefania; Cucchiara, Federico; Marconcini, Riccardo; Bulleri, Alessandra; Manacorda, Simona; Capuano, Annalisa; Cioni, Dania; Nuzzo, Amedeo; de Jonge, Evert; Mathjissen, Ron H. J.; Neri, Emanuele; van Schaik, Ron H. N.; et al. (Frontiers in Molecular Biosciences, 2024)
Introduction: Immune checkpoint inhibitors (ICIs) represent the standard therapy for metastatic melanoma. However, a few patients do not respond to ICIs and reliable predictive biomarkers are needed.Methods: This pilot study investigates the association between mRNA levels of programmed cell death-1 (PD-1) ligand 1 (PD-L1), interferon-gamma (IFN-γ), and transforming growth factor-β (TGF-β) in circulating extracellular vesicles (EVs) and survival in 30 patients with metastatic melanoma treated with first line anti-PD-1 antibodies. Blood samples were collected at baseline and RNA extracted from EVs; the RNA levels of PD-L1, IFN-γ, and TGF-β were analysed by digital droplet PCR (ddPCR). A biomarker-radiomic correlation analysis was per-formed in a subset of patients.Results: Patients with high TGF-β expression (cut-off fractional abundance [FA] >0.19) at baseline had longer median progression-free survival (8.4 vs 1.8 months; p=0.006) and overall survival (17.9 vs 2.63 months; p=0.0009). Moreover, radiomic analysis demonstrated that patients with high TGF-β expression at baseline had smaller lesions (2.41 ± 3.27 ml vs 42.79 ± 101.08 ml, p<0.001) and higher dissimilarity (12.01 ± 28.23 vs 5.65 ± 8.4; p=0.018).Discussion: These results provide evidence that high TGF-β expression in EVs is associated with a better response to immunotherapy. Further investigation on a larger patient population is needed to validate the predictive power of this potential biomarker of response to ICIs.